VIROLOGICAL AND MOLECULAR-BIOLOGICAL METHODS OF DIAGNOSING CYTOMEGALOVIRUS INFECTION - Daminov F. A.; Djabbarova N. R.; Xolikulova G.A. (Web of Journals Publishing, 2025)
The gold standard is the determination of CMV in cell culture. As a rule, human foreskin fibroblast cells are used for this purpose. Blood, urine, saliva, cervical-vaginal secretion, cerebrospinal fluid, BAL and tissue from biopsy specimens are the materials for the study. Reproduction of CMV in cell culture is accompanied by a characteristic CMV-associated cytopathic effect [7,8,9].
Keywords: Diagnosis, identification, verification, cytomegalovirus infection, immunofluorescence analysis.